Spectators' perceptions of esports tourism - Özgürel, Gizem; Aydın, Nercü Durmuş; Çilesiz, Emre; Ünal, Aydın; Çelen, Onur (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The aim of this study was to identify how the concept of "eSports tourism", which combines the concepts of "eSports" and "tourism," is conceptualized through metaphors by participants of this form of tourism. To achieve this, a phenomenological research design was preferred as a qualitative research method. A total of 656 individuals (n=656; 594 males and 62 females) who had participated in eSports tourism at least once were reached. Participants from various gaming platforms and communities were asked to complete a semi-structured form containing the expression "eSports tourism is like... because...". The metaphors obtained were coded using MaxQDA 2020 software and categorized into six main themes. The findings reveal that eSports tourism is most commonly associated with the themes of "Technology" (29.3%) and "Entertainment" (26.2%). It was determined that the vast majority of participants were male (90.54%) and that they had typically participated in eSports tourism once (67.37%). The most preferred game types were found to be First Person Shooter (FPS) and Multiplayer Online Battle Arena (MOBA). It was concluded that eSports tourism, while based on technological infrastructure, offers an entertainment-oriented experience, and also carries cultural and social dimensions.